Factors influencing infections caused by Extended Spectrum Beta Lactamase (ESBL) producing bacteria in patients with urinary tract infections at RSUD dr. R. Soetijono Blora - Endrawati, Endrawati; Sutiningsih, Dwi; SA, Mateus (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2023)
Urinary tract infection (UTI) is a bacterial infection that is often found in pediatric patients. The prevalence of infections due to ESBL-producing Enterobacterales is increasing worldwide. This study aims to identify and analyze the factors that influence Extended Spectrum Beta Lactamase (ESBL) producing bacteria in UTI patients at RSUD dr. R. Soetijono Blora. A cross-sectional study has been carried out at RSUD dr. R. Soetijono Blora in January-March 2023. The results of this study showed that 58 respondents with urine culture results found Enterobacterales pathogenic bacteria. Based on the sensitivity test for the Extended Spectrum Beta Lactamase (ESBL) enzyme producer, 39 people (67.2%) were categorized as ESBLs and 19 people (32.8%) Non-ESBLs. The study variables included age, gender, history of catheter insertion, history of stones or urinary tract surgery and history of taking antibiotics in the last 6 months. The chi-square test to determine the relationship between variables was used to determine significant risk factors. Bivariate logistic regression showed that history of catheter insertion and history of use of antibiotics in the last 6 months were significant risk factors. Prevalence of UTIs due to ESBL-producing Enterobacterales in RSUD dr. R. Soetijono Blora is high and the wise use of antibiotics, especially the third generation cephalosporins as therapy, is needed for preventive strategies to reduce antibiotic resistance